Harmonization of Aviation Safety and Security Legal Regulation in the European Union: Impact on the Global Convergence of Aviation Law - Stonkus, Saulius (Teisė, 2022)
This paper deals with civil aviation, which is highly international. Therefore, harmonization of regulation in this area on a global scale is inevitable, which means that aviation law requires an integrated approach. However, only slightly over half of the countries fully comply with the standards issued by the International Civil Aviation Organization for basic international aviation regulation, which poses a serious threat to aviation safety and security. In this respect, the integrative nature of the European Union offers us to look at the Union’s activities in the context of aviation regulation. The aim of this paper is to investigate the impact that the harmonization of civil aviation safety and security regulations in the EU has on the development of global aviation regulations. The paper provides a more detailed analysis of the beginning and further integration of the EU’s internal aviation market and the formation of the Union’s external policy in this area, which has played a key role in harmonizing the legal framework for aviation safety and security. The study revealed the preconditions for the harmonization of aviation safety and security rules in the European Union highlighted the essential features of this process and its impact on the convergence of aviation regulation on a wider scale (beyond the EU).